Entropy and structure: Re-thinking the Plaza de Armas building as Modernist heritage - Armando Caroca Fernández (Materia Arquitectura)
Buildings, as all things, age. They are not static entities, but change, get wrinkled, get stained. In that sense, their behavior resembles that of living organisms but, generally, these changes are seen as a decline, as processes that ought to be avoided. What would happen if we began to think about buildings as dynamic systems affected by entropy, in such way that the passing of years actually adds value to them The paper illustrates the case of the Plaza de Armas building, built in 1954 in the foundational center of Santiago de Chile, a building that turns paradigmatic in two ways: as an example of the introduction of the modernist ideals in the country and as an often cited example of “bad aging”. It is then proposed to imagine a possible refurbishment, reformulating traditional ideas of heritage preservation. This new approach will allow to re-insert this structure into the ever-changing fabric of urban centers, so that the building can evolve into useful heritage for the city in which it is located.